Development of 2NN MEAM potential for Fe–Al and atomistic investigation of surface and interface properties of the inhibition layer in galvanized Fe. (1st June 2022) - Chen, Kefan; Mun, Sungkwang; Baskes, Michael; Horstemeyer, Mark; Li, Bin
Abstract: Hot-dip Zn coating or galvanizing is an important process for high strength steels that are extensively used in automotive industries. During galvanizing, Fe in the steel substrate quickly reacts with Al that is dissolved in the Zn bath and an inhibition layer is formed. To better understand the formation of the inhibition layer that occurs on a small scale (typically ∼100 nm), it is necessary to understand the physical properties of the interfacial phases on the atomic scale. In the present work, we develop a second nearest neighbor Fe–Al modified embedded atom method (MEAM) potential to calculate the surface and interface properties of the inhibition layer. The as-developed potential is able to well describe the complex crystal structure of the inhibition layer. Also, this potential satisfies three criteria for the experimentally observed phases: phase stability, convex hull, and elastic stability. The calculation results show a negative interfacial energy between Fe and the inhibition layer, a manifestation of the high affinity between Fe and Al. The formation of the inhibition layer on the Fe surface lowers the interfacial energy. Our results also show that the crystal orientation of Fe strongly affects the interfacial energy, and the (110) plane gives the lowest interfacial energy. The work of adhesion is also calculated with the developed MEAM potential, and the results agree well with the results obtained by other methods.